Evaluation of production and fruit quality of a yellow passion fruit cultivar infected with the cowpea aphid-borne mosaic virus - Gomes, Francielly Rodrigues [UNESP] (2022)
This work aimed to characterize and evaluate the correlations between fruit and pulp characteristics of a commercial cultivar of yellow passion fruit (FB 200) infected with the cowpea aphid-borne mosaic virus (CABMV). The observation of natural infection occurred after the beginning of flowering. The parameters weight, length, and diameter, peel thickness, pulp yield, soluble solids content, titratable acidity, and the soluble solids content/titratable acidity ratio were evaluated. A completely randomized block design composed of 20 plots with five replications was adopted. The data were subject to descriptive analyses and Pearson’s Correlation at 1 and 5% of significance. CABMV has decreased the quality and physical characteristics of fruits, but they still could be destined for juice processing industries. Many parameters of the fruits presented significant positive correlations.